EARLY JURASSIC TO EARLY LATE CRETACEOUS RADIOLARIANS FROM THE SANTA ROSA ACCRETIONARY COMPLEX (NORTHWESTERN COSTA RICA) - Bandini, Alexandre Nicolas; Baumgartner, Peter Oliver; Flores, Kennet; Dumitrica, Paulian; Jackett, Sarah-Jane (Ofioliti, 2011)
In the circum-Pacific ophiolitic belts; when no other biogenic constituents are found; radiolarians have the potential to provide significant biostratigraphic information. The Santa Rosa Accretionary Complex; which crops out in several half-windows (Carrizal; Sitio Santa Rosa; Bahia Nancite; Playa Naranjo) along the south shores of the Santa Elena Peninsula in northwestern Costa Rica; is one of these little-known ophiolitic mélanges. It contains various oceanic assemblages of alkaline basalt; radiolarite and polymictic breccias. The radiolarian biochronology presented in this work is mainly based by correlation on the biozonations of Carter et al. (2010); Baumgartner et al. (1995b); and O’Dogherty (1994) and indicate an Early Jurassic to early Late Cretaceous (early Pliensbachian to earliest Turonian) age for the sediments associated with oceanic basalts or recovered from blocks in breccias or megabreccias. The 19 illustrated assemblages from the Carrizal tectonic window and Sitio Santa Rosa contain in total 162 species belonging to 65 genera. The nomenclature of tectonic units is the one presented by (Baumgartner and Denyer; 2006). This study brings to light the Early Jurassic age of a succession of radiolarite; which was previously thought to be of Cretaceous age; intruded by alkaline basalts sills (Unit 3). The presence of Early Jurassic large reworked blocks in a polymictic megabreccia; firstly reported by De Wever et al. (1985) is confirmed (Unit 4). Therefore; the alkaline basalt associated with the radiolarites of these two units (and maybe also Units 5 and 8) could be of Jurassic age. In the Carrizal tectonic window; Middle to early Late Jurassic radiolarian chert blocks associated with massive tholeitic basalts and Early Cretaceous brick-red ribbon cherts overlying pillow basalts are interpreted as fragments of a Middle Jurassic oceanic basement accreted to an Early Cretaceous oceanic Plate; in an intra-oceanic subduction context. Whereas; the knobby radiolarites and black shales of Playa Carrizal are indicative of a shallower middle Cretaceous paleoenvironment. Other remnants of this oceanic basin are found in Units 2; 6; and 7; which documented the rapid approach of the depocentre to a subduction trench during the late Early Cretaceous (Albian-Cenomanian); to possibly early Late Cretaceous (Turonian).